2022
DOI: 10.1007/s11135-022-01425-6
|View full text |Cite
|
Sign up to set email alerts
|

Criminological scoping reviews as part of a student assignment: methodological considerations

Abstract: In this article we reflect on the use of a scoping review method in the course of a student assignment. In total, 24 scoping reviews were conducted on police research topics, following the same procedure with similar yet topic-specific review protocols. We discuss each of the eight phases of the scoping review method and provide examples and good practices on how to conduct these steps. We also focus on difficulties that were experienced and how to overcome them in future scoping reviews. The aim of this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Feys and Verhage, 2019;Gilleir, 2013;Rummens et al, 2017). This is probably the result of some limitations regarding the use of keywords and databases to which the scoping reviews were subject (see Feys, 2022a). Undeniably, more research would have been found if more police decision-making topics had been included (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Feys and Verhage, 2019;Gilleir, 2013;Rummens et al, 2017). This is probably the result of some limitations regarding the use of keywords and databases to which the scoping reviews were subject (see Feys, 2022a). Undeniably, more research would have been found if more police decision-making topics had been included (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We chose this method because of our intention to explore the extent and nature of police decision-making research, summarize the available literature on the different topics included and the methodology used in these studies with the overall aim to identify gaps in the literature (Arksey and O'Malley, 2005;Munn et al, 2018). All scoping reviews followed the method developed by the first author of this article ( Feys, 2022a), which consists of eight steps. We recommend readers to consult the original article for a fuller discussion on the method and its application to the student assignment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although quality assessments are not typically included in scoping reviews (Arksey and O'Malley, 2005;Levac et al, 2010;Feys, 2022;Peters et al, 2015aPeters et al, , 2015b, we included them to provide recommendations for practice, policy, and future research (Daudt et al, 2013;Colquhoun et al, 2014;Khalil et al, 2016;Peters et al, 2015b). To ensure that all insights were considered, we assigned weights to studies without excluding those of lower quality (Feys & Verhage, 2018;Hannes, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The interrater agreement between the two authors for the final classification of studies to be included in the review 2 was almost perfect, with Cohen’s Kappa = 0.88, in accordance with established guidelines (Landis & Koch, 1977). Additional studies were included through reference mining, with the first author identifying six additional studies based on the references cited in the shortlisted studies (Arksey & O’Malley, 2005; Feys, 2022; Peters et al, 2015a). Four further studies were included by the first author through purposive sampling, which is a recognized method for ensuring broad coverage of the literature (Ames et al, 2019; Dixon-Woods et al, 2006).…”
Section: Methodsmentioning
confidence: 99%